Tin Fruit: Types and Benefit - Rachmat Faisal Syamsu; Rahmawati Mamile (Indonesian Journal of Global Health Research, 2025)
This study explores the potential and therapeutic benefits of the tin plant (Ficus carica L.), widely recognized in traditional Arabic medicine for its health-promoting properties. Objective: Known as an antioxidant and anticancer agent, tin fruit contains phenols, flavonoids, terpenoids, and alkaloids, which play a role in combating various diseases, including cancer, gastrointestinal disorders, cardiovascular conditions, and inflammation. Method: Utilizing a library research method, the study collects data from books, journals, and scientific articles to analyze the medicinal properties and cultivation of tin plants. Results: Results highlight the rich bioactive compounds present in different varieties, such as Iraqi, Brown Turkey, Green Jordan, and Red Palestine, which are shown to address health issues like diabetes, respiratory ailments, kidney stones, and tumors. The findings also reveal the adaptability of the tin plant to diverse climates, making it a promising candidate for agricultural development in tropical regions like Indonesia. Conclusions: The study concludes that tin fruit cultivation not only supports public health but also offers economic benefits through its use in producing food and herbal medicine. These findings underline the significance of promoting tin cultivation and utilization in modern health and agricultural practices.